EFEITOS AGUDOS DO TERERÉ (Ilex paraguariensis) SOBRE O DESEMPENHO AERÓBIO DE CORREDORES DE RUA: UM ESTUDO CLÍNICO RANDOMIZADO DUPLO-CEGO - Raphael De Jesus Brittes (2024)
Introduction: In some regions of Brazil and Paraguay, yerba mate (Ilex paraguariensis) is consumed in an infusion with cold water, known as Tereré. Tereré contains polyphenols, caffeine, and other compounds identified in the literature as beneficial for physical performance. However, there are limited studies on yerba mate (EM) consumed in its traditional form within the context of sports, highlighting the need for further research. Objectives: To evaluate the acute effects of Tereré (yerba mate) ingestion on the aerobic physical performance of street runners. Materials and Methods: In a randomized, double-blind, cross-over design (wash-out period of 7 to 14 days), ten men (31.3 ± 8.03 years, 173.55 ± 5.76 cm, 74.38 ± 10.23 kg, body fat percentage: 15.94 ± 4.24%) and nine women (32.78 ± 5.15 years, 163.22 ± 4.47 cm, 56.8 ± 6.4 kg, body fat percentage: 20.55 ± 7%) consumed a total of 50 g of traditional yerba mate (TrrEx) or decaffeinated yerba mate (TrrPL) diluted in cold water (6 mL/kg). Two hours after ingesting a standardized meal, participants consumed the beverage (TrrEx or TrrPL) and, after 60 minutes, performed a treadmill test using a gas metabolic analyzer to determine running economy (ECO) and respiratory quotient (RQ), followed by a maximal incremental test to determine peak oxygen consumption (VO2 Peak ), anaerobic threshold (LAn), and respiratory compensation point (RCP). Results: Despite a slight increase in mean values for AT (+0.69% for men and +3.22% for women), RCP (+0.02% for men and +0.26% for women), and VO2 Peak (+0.69% for men and +2.48% for women) in the TrrEx group compared to the TrrPL group, there were no statistically significant differences between the experimental conditions for VO2 Peak , LAn, RCP, RQ, and ECO. Conclusion: The ingestion of Tereré did not alter ECO, RQ, VO2 Peak , LAn, or RCP compared to the TrrPL group in both sexes (p > 0.05), although the effect size for VO2 Peak was small for women. Tereré ingestion did not induce significant changes in metabolic and running performance parameters.